Quality of Fermented Coffee Skin Waste with Several Types of Probiotics and Fermentation Time - I Dewa Nyoman Sudita; I Gusti Agus Maha Putra Sanjaya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Coffee skin waste, which is abundant in Bali's coffee-producing regions, has not been utilized and has become a public health hazard. Therefore, it is necessary to make an effort to utilize it as a beneficial raw material for animal feed, while simultaneously enhancing its quality through fermentation. Using various types of probiotics, the research conducted seeks to improve the quality of the fermentation of coffee skin waste. The study employed a completely randomized design with four kinds of probiotics: EM-4 (P1), Bio Bali Tani (P2), MOL from coffee husk (P3), and Aspergillus niger (P4), with each treatment being administered three times. In weeks 1, 2, and 3, the grade of the fermented product was evaluated in the laboratory. The results demonstrated that fermentation of coffee skin residue improved the quality of coffee skin by reducing the crude fiber content from 27.17–29.46% to 19.18–19.44% and increasing the crude protein content from 9.53–10.23% to 11.56–17.67%. The optimal fermentation period was 2 weeks, with a protein concentration of 14.67%, which was significantly different (P 0.05) from 1 week and 3 weeks. It was statistically significant (P 0.05) that LMO probiotics were 16.67% higher than EM-4 probiotics, Bio-Bali Tani, and Aspergillus niger probiotics. It can be concluded that the fermentation of coffee skin waste as animal feed can enhance the crude protein (CP) content, with local microorganisms (LMO) and a fermentation time of two weeks being optimal.